ANALYSIS OF COMMUNITY WOMEN AND DEVELOPMENT ACTIVITIES IN ONA -ARA LOCAL GOVERNMENT AREA OF OYO STATE - A W Ajetunmobi; M G Olujide; O A Akinsorotan; B A.R Carew (Journal of Agricultural Extension, 2015)
This study investigated the roles of Community Women and Development (COWAD) to women's development, participation in their programmes, constraints to such participation and indicators of respondents' (participants) derived benefits, using 80 selected COWAD members. The findings indicate that COWAD contributes to women development in the areas of providing improved agricultural machinery, income generating activities, skill development and adult literacy. The major constraint to participation is inadequate fund, but level of participation in COWAD's activities and respondents age are the highest indicators of benefits derived from COWAD's activities. Assistance to COWAD should, therefore, be in the area of funding, while COWAD itself should focus more of its activities on people's felt needs.